Gordon Scott Fulcher: Renaissance Man of Glass Science - Mauro, John C. (Frontiers in Materials, 2014)
To a glass scientist, the name “Fulcher” conjures images of viscosity vs. temperature diagrams for glass-forming liquids. Indeed, Gordon Fulcher’s seminal 1925 publication, in which he proposed his three-parameter model of viscosity, is one of the most significant and influential papers ever published in the field of glass science. Fulcher developed this equation during the early part of his 14-year career at Corning Glass Works (1920-1934). However, Fulcher’s work in viscosity represents a small fraction of his highly diverse and accomplished career, which included pioneering the field of electrocast ceramics and developing the modern system of scientific abstracting that it still in use today. Fulcher also had a keen interest in social and economic problems, and his latter research focused heavily on the field of metacognition, i.e., the process of thinking.